Model misspecification, the equilibrium natural interest rate and the equity premium - Oreste Tristani (European Central Bank (ECB), 2007)
This paper analyses the determinants of the natural rate of interest in a non-linear model where agents are uncertain over both future technology growth and the future course of monetary policy. I show that the real natural rate can be affected by sizable uncertainty premia, including premia associated with monetary un-certainty. This result is potentially problematic for both the estimation of the natural rate and its use as a policy indicator. Monetary uncertainty can also contribute to amplify the equity premium, and to account for its apparent, positive link with inflation.
Keywords: E43; G11; 330; equity premium puzzle; model misspecification; Natural rate of interest; risk-free rate puzzle; robust control; Zins; Risikoprämie; Zinstheorie; Geldpolitik; Sparen; Modellierung; Theorie; USA